An experimental study on the role of inter-particle friction in the shear-thinning behavior of non-Brownian suspensions. Issue 25 (14th June 2021) - Arshad, Muhammad; Maali, Abdelhamid; Claudet, Cyrille; Lobry, Laurent; Peters, Francois; Lemaire, Elisabeth
Abstract : AFM is used to measure the normal load variation of the friction coefficient, μ, of two contacting polystyrene particles (40 μm in diameter). The observed decrease of μ provides an explanation for the shear-thinning behavior of non-Brownian suspensions made of the same particles. Abstract : This paper focuses on shear-thinning in non-Brownian suspensions. In particular, it proposes a quantitative experimental validation of the model proposed by Lobry et al. [ J. Fluid Mech., 2019, 860, 682–710] that links viscosity to microscopic friction between particles and, in particular, shear-thinning to load-dependent friction coefficient. To this aim, Atomic Force Microscopy (AFM) is used to measure the pairwise friction coefficient of polystyrene particles (40 μm in diameter), immersed in a Newtonian liquid, for different normal loads ranging from 10 to 1000 nN. It is shown that the inter-particle friction coefficient decreases with the load, contrarily to what is expected for macroscopic contacting bodies. The experimental friction law is then introduced into the viscosity model proposed by Lobry et al. and the results are compared to the viscosity of suspensions made of the same particles dispersed in the same liquid as those used for AFM measurements. The very good agreement between the measured viscosity values and those predicted by the model of Lobry et al. with the friction coefficient measured by AFM as input data shows the relevance of the scenario proposed by Lobry et al. and highlights the close links between the microscopic friction properties of the particles and the macroscopic rheological behavior of suspensions.